Incidence of clindamycin resistance in clinical isolates of Staphylococcus aureus - Debmita Debdas; Sangeeta Joshi (Journal of Infection in Developing Countries)
Clindamycin is used in Staphylococcal infections and resistance patterns to Clindamycin vary between institutions. Inducible Clindamycin resistance is detected by the CLSI recommended D-test. This study was done to estimate the incidence of constitutive and inducible Clindamycin resistance in our hospital. Three hundred and seventy nine S.aureus isolates from clinical specimens collected over 6 months were tested for Clindamycin resistance using the D-test. Fourteen percent were Clindamycin resistant and among them 43% showed the inducible phenotype. Clindamycin resistance was higher among MRSA isolates (p < 0.001). It was concluded that Clindamycin should not be used empirically in serious Staphylococcal infections and that such studies are necessary to guide empiric therapy.